Catalan, immigrants and charnegos: “race”, “cultura” and “mixture” in Catalan Nationalist Rhetoric - Clua i Fainé, Montserrat (Revista de Antropología Social, 2011)
This paper focuses on the manner in which ‘race’ and ‘culture’ are used in nationalist rhetorics, paying special attention to the presence or absence of ideas of biological or cultural ‘mixture’ employed in order to define socio-political identity of offspring of parents who possess different national identities. I will analyze this phenomenon in the ethnographic instance of Catalan nationalism, a kind of ‘civic’ nationalism that defines Catalan identity basically in cultural terms. The paper proposes to contrast this type of nationalist rhetoric with a form of xenophobic attitude that developed in Catalonia in the past century —1960s- 1970s— and which served to stigmatize the offspring of ‘mixed’ marriages between Catalans and Spanish immigrants. This instance serves to show that nationalist ideologies tend to adapt their argumentative structure to the prevailing socio-political and conceptual context, shifting from and/or combining culturalist and biologist/essentialist principles of classification. Finally, I want to point out the importance of paying special attention to the contemporary economic crisis in particular, with regard to attitudes and disqualifications of non- European immigrants in Catalonia and their descendants.
Keywords: Race; culture; mixture; social classification; Catalan nationalism; charnego; immigration; mixed-marriage; Catalonia